THE EFFECTIVENESS OF TWO-STAY TWO-STRAY TECHNIQUE TO TEACH NARRATIVE TEXT WRITING - Prastika, Mely Azini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research was conducted to find out the effectiveness of two-stay two-stray (TSTS) technique to teach narrative text writing on the tenth grade students of SMA N 1 Seponti Jaya in academic year 2016/2017. The purposes of this research were to find out whether the use of Two-Stay Two-Stray Technique is effective or not to teach narrative text writing and to find out the effectiveness of Two-Stay Two-Stray Technique in improving the students’ writing achievement. The method used in this research was quasi-experimental study. The samples were taken from class B as the experimental group and class C as the control group by using cluster sampling. The data were collected by using measurement technique and the tool of data collecting was written test. Based on the calculation, the t-obtained was 14.55 where the degree of freedom was 2.021. It can be seen that the t-obtained was higher than the t-critical. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The effectiveness of the treatment was found by calculating the effect size, and the result of the effect size was 2.91 that categorized as strong effect. Keywords: Narrative text writing, Two-Stay Two-Stray Technique, Quasi-experimental study